Information security and cryptology – ICISC 2014 : 17th International Conference, Seoul, South Korea, December 3-5, 2014, Revised selected papers /: 17th International Conference, Seoul, South Korea, December 3-5, 2014, Revised selected papers. (2015) - Unknown
No abstract available